THE IMPACT OF CHINESE WHISPER GAME AND VOCABULARY MASTERY ON STUDENTS’ SPEAKING SKILL - Suryadi Suryadi (Universitas Tanjungpura, 2022)
The study's goal was to see how the Chinese whisper game and vocabulary practice affected the students' ability to communicate in English. The experimental approach was being used in this study. A 2x2 factorial design is used in research. Data on learning outcomes were gathered through pre- and post-testing activities. There were 280 students in the class of X MA Negeri 1 Serang, and a random sample of 80 students were chosen to participate in the study. Experiment and control groups were significantly different at the posttest, according to the results of this study. For the FO, the value is 5.225, whereas for the Significance, the number ranges from 0.025 < 0.05. This shows that the null hypothesis has been rejected and the research hypothesis has been validated. For students' capacity to communicate effectively in English, this suggests a distinction between the effects of playing Chinese whisper games and learning vocabulary